Untargeted muscle tissue metabolites profiling in young, adult, and old rats supplemented with tocotrienol-rich fraction - Saud Gany, Siti Liyana; Tan, Jen Kit; Chin, Kok Yong; Hakimi, Nur Haleeda; Ab Rani, Nazirah; Ihsan, Nurhazirah; Makpol, Suzana (Frontiers in Molecular Biosciences, 2022)
The greatest significant influence on human life span and health is inevitable ageing. One of the distinguishing characteristics of ageing is the gradual decrease of muscle mass and physical function. There has been growing evidence that tocotrienol can guard against age-associated chronic diseases and metabolic disorders. This study aimed to elucidate the effects of tocotrienol-rich fraction (TRF) on muscle metabolomes and metabolic pathways in ageing Sprague Dawley (SD) rats. Three months, nine months, and twenty-one months old male SD rats were divided into control and treated groups with 10 rats per group. Rats in control and treated groups were given 60 mg/kg body weight/day of palm olein and 60 mg/kg body weight/day of TRF, respectively, via oral gavage for three months. Muscle performance was assessed at 0 and 3 months of treatment by measuring muscle strength and function. Our results showed that TRF treatment caused a significant increase in the swimming time of the young rats. Comparison in the control groups showed that metabolites involved in lipid metabolisms such as L-palmitoyl carnitine and decanoyl carnitine were increased in ageing. In contrast, several metabolites, such as 3-phosphoglyceric acid, aspartic acid and aspartyl phenylalanine were decreased. These findings indicated that muscle metabolomes involved in lipid metabolism were upregulated in aged rats. In contrast, the metabolites involved in energy and amino acid metabolism were significantly downregulated. Comparison in the TRF-supplemented groups showed an upregulation of energy and amino acid metabolism metabolites. Metabolites such as N6-methyl adenosine, spermine, phenylalanine, tryptophan, aspartic acid, histidine, and N-acetyl neuraminic acid were up-regulated, indicating promotion of amino acid synthesis and muscle regeneration. Energy metabolism was also improved in adult and old rats with TRF supplementation as indicated by the upregulation of nicotinamide adenine dinucleotide and glycerol 3-phosphate compared to the control group. In conclusion, the mechanism underlying the changes in skeletal muscle mass and functions in ageing was related to carbohydrate, lipid and amino acid metabolism. Tocotrienol supplementation showed beneficial effects in alleviating energy and amino acid synthesis that may promote the regeneration and renewal of skeletal muscle in ageing rats.